Dynamics Of Viral Advertising - Binay Kurultay, Ayşe (The Turkish Online Journal of Design Art and Communication, 2012)
Digital technologies have heightened the debate on convergence where technologies, corporations and people [target audiences] meet. New media has become a new meeting place and a social platform for people. As more brands choose to employ relationship marketing strategies that emphasize consumer’s experience with the brand, it is inevitable that they explore opportunities to connect with their target audiences in this new meeting place. Thus, user-created content and electronic word of mouth [eWOM] have become important concepts for influential and noteworthy advertising campaigns in this new medium. The aim of this study is to understand the dynamics of viral marketing campaigns and to identify the strategies that make viral advertising successful. International cases, such as brand applications of 3D Mapping Projections are used to understand the relationship between cutting-edge digital art and their use in advertisements. Recent Turkish viral ad campaigns such as Profilo’s “O Tabak Bitecek!” [Finish everything on your plate] and Turkish Airlines Miles and Smiles’ “İnanılmaz Evlenme Teklifi” [Unbelievable Proposal] disseminated through social networks are used as cases to identify the message strategies used in making these advertisements successful.
Keywords: Advertising; Viral Advertising; 3D mapping projection; Branding; reklam; Viral Reklam; 3D Haritalama Projeksiyon; Markalaşma